A rare case report of twin reversed arterial perfusion sequence in monochorionic diamniotic twin and outcome of Dr. Pump and Mr. Acardiac acephalus in a tertiary care centre - Thirupathi, Kalaivani; M. Meganathan, Jayalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Twin reversed arterial perfusion (TRAP) sequence or Acardiac twinning is a rare complication seen in monozygotic gestation. The reported incidence of Acardiac twin is 1 in 35000 births and 1 in 100 monozygotic twin gestation. In monochorionic twin pregnancies, a twin with poorly developed heart and upper torso (the “Acardiac”) is perfused by its co-twin (the “pump”) via superficial arterio-arterial or veno-venous anastomoses located on the placental surface, through which blood pumped backwards. Due to poor prognosis of TRAP sequence in monochorionic pregnancies, 100% mortality was reported in Acardiac twin due to its severe malformations and also due to heart failure and prematurity in pump twin 50-55% mortality was reported. We hereby report a case of 22-year-old primigravida, monochorionic diamniotic (MCDA) twins presented with abruption at 24 weeks of gestation, resulted fetal demise of pump twin. Our study also reviewed necessity of thorough sonological evaluation and therapeutic opportunities in monochorionic multifetal pregnancies.